Pengendalian Terpadu Hama dan Penyakit Tanaman Semusim di Desa Tanjung Seteko Kecamatan Indralaya Kabupaten Ogan Ilir: Integrated Control of Pests and Diseases of Seasonal Plants in Tanjung Seteko Village, Indralaya District, Ogan Ilir District - Muslim, Ahmad; Suwandi, Suwandi; Irsan, Chandra; Pratama, Rahmat; Arsi, Arsi; Saripudin, Saripudin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
In the North Indralaya sub-district, annual crop agriculture, including annuals, melons, and watermelons, relies on conventional cultivation methods using expensive synthetic chemical fertilizers and pesticides to enhance production and combat pests and diseases. This community service initiative aims to educate and implement integrated control practices for sustainable annual crop cultivation while providing knowledge on pest and disease management in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency. The project, part of Sriwijaya University's integrated community service program, seeks to transform the village into a vegetable center in Ogan Ilir. The activities involve socializing integrated control methods through focused group discussions, practical sessions on biostimulant preparation, and field application. Farmers actively participate, posing questions about optimal annual crop cultivation and integrated control solutions. Preliminary results indicate that combining biostimulants with integrated control effectively manages pests and plant diseases. Continued intensive support aims to enable farmers in Tanjung Seteko village to adopt integrated control practices successfully, contributing to the village's potential as a vegetable center in Ogan Ilir.